Cervical articular process joint osteochondrosis in Warmblood foals. (21st February 2020) - Bergmann, Wilhelmina; de Mik‐van Mourik, Marjolijn; Veraa, Stefanie; van den Broek, Jan; Wijnberg, Inge D.; Back, Willem; Gröne, Andrea
Abstract: Background: In Warmblood horses, degenerative joint disease is involved in cervical malformation and malarticulation (CVM). The degree of contribution of articular process joint (APJ) osteochondrosis (OC) is not clear. Objectives: (a) To explore the presence of predilection sites for APJ OC in cervical and cranial thoracic vertebral columns of Warmblood foals and (b) to examine the correlation of such a site with the predilection site of CVM. Study design: Case series. Methods: Seven hundred APJ facets of C2 to T2 of 29 foals (11 months gestation to 12 months [median age 7 days; range 365 days; 95% confidence interval [95% CI] 2‐47 days]) were examined for OC and prevalence between joints, and the predilection site for CVM and the cranial cervical vertebral column were evaluated. Results: About 20.6% of facets revealed OC. There was no predilection site. Prevalence decreased with age up to 1 year (odds ratio [OR] 0.997; (95% CI 0.975‐0.998)) but not up to 5 months. Severity increased with age in all age ranges (up to 1 year OR 1.023; 95% CI 1.005‐1.049; >1‐5 months, OR 1.203; 95% CI 1.014e+00‐1.921; up to 1 month, OR 1.114; 95% CI 1.041‐1.228). Highest prevalence was in cranial facets of the cervical and cervical‐thoracic joints and in caudal facets of the thoracic joint up to 1 year and up to 1 month (OR 0.364; 95% CI 0.170‐0.745, OR 0.434; 95% CI: 0.235‐0.782, OR 7.665; 95% CI: 1.615‐66.553 and OR 0.400; 95% CI 0.170‐0.880, OR 0.351; 95% CI 0.172‐0.700, OR 5.317; 95% CI 1.098‐44.344 respectively). Main limitations: Two‐thirds of the foals were less than 1 month of age. Conclusions: Articular process joint OC in Warmblood foals is common and is not more prevalent at CVM predilection sites, suggesting that abnormalities of enchondral ossification may not be major contributors to CVM.